2022
DOI: 10.1002/smll.202204809
|View full text |Cite
|
Sign up to set email alerts
|

Nanozyme‐Enabled Treatment of Cardio‐ and Cerebrovascular Diseases

Abstract: Cardio‐ and cerebrovascular diseases are two major vascular‐related diseases that lead to death worldwide. Reactive oxygen species (ROS) play a vital role in the occurrence and exacerbation of diseases. Excessive ROS induce cellular context damage and lead to tissue dysfunction. Nanozymes, as emerging enzyme mimics, offer a unique perspective for therapy through multifunctional activities, achieving essential results in the treatment of ROS‐related cardio‐ and cerebrovascular diseases by directly scavenging ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 110 publications
(132 reference statements)
0
22
0
Order By: Relevance
“…Recently, nanomedicine has been rapidly developed and extensively studied in the treatment of atherosclerosis due to its good biocompatibility as well as therapeutic effects. Since ROS play an important role in the development of atherosclerosis, nanoceria with biomimetic characteristics of various enzymes (catalase, superoxide oxidase, etc.) can effectively scavenge intracellular and intraorganic ROS and have great potential in the treatment of atherosclerosis. Therefore, increasing the antioxidant activity of the nanoceria becomes the key to achieving the highly efficient atherosclerosis treatment. Generally, in addition to the surface area and crystal face, the catalytic performance of nanoceria against ROS is mainly determined by the level of structural defects due to oxygen vacancies, as indexed using the surface Ce 3+ fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanomedicine has been rapidly developed and extensively studied in the treatment of atherosclerosis due to its good biocompatibility as well as therapeutic effects. Since ROS play an important role in the development of atherosclerosis, nanoceria with biomimetic characteristics of various enzymes (catalase, superoxide oxidase, etc.) can effectively scavenge intracellular and intraorganic ROS and have great potential in the treatment of atherosclerosis. Therefore, increasing the antioxidant activity of the nanoceria becomes the key to achieving the highly efficient atherosclerosis treatment. Generally, in addition to the surface area and crystal face, the catalytic performance of nanoceria against ROS is mainly determined by the level of structural defects due to oxygen vacancies, as indexed using the surface Ce 3+ fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Neural apoptosis also results in ischemia reperfusion injury to the brain. 161 A multi-enzyme cascade antioxidant system was just recently created to reduce intracellular ROS and prevent neuronal apoptosis during cerebral ischemic reperfusion injury (CIRI) by Liu and colleagues. They were able to successfully create the Fe 2 NC@Se nanozyme, which had good cytoprotective properties and three different types of antioxidant activities.…”
Section: Nanozyme In Non-oncologic Therapymentioning
confidence: 99%
“… 59 60 61 Thus, MNPs have both drug-carrying and self-therapeutic efficacy for treating various inflammatory diseases ( Table 1 ). 45 59 60 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 In this review, we discuss the roles of recently reported MNPs in the scavenging of reactive oxygen species (ROS) and in anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%